IMPROVING STUDENTS’ ABILITY IN WRITING PROCEDURE TEXT THROUGH MIND MAPPING TECHNIQUE USING PICTURE SERIES AT CLASS XI OF SMKN 1 KAMIPANG - Rahmanti, Kitri; Usadiati, Wahjuningsih; Karani, Elanneri (Program Studi Magister Pendidikan Bahasa Inggris, Program Pascasarjana, Universitas Palangka Raya, 2020)
The present research aimed at finding out how mind mapping using picture series can make students interested in teaching and learning process of writing and finding out whether the application of mind mapping using picture series could improve students’ skill in writing procedure text at class XI SMKN 1 Kamipang in the Academic Year 2019-2020. To reach the aims of the research, the researcher used a classroom action research design where the researcher asked the students’ responses and did action research with the application of mind mapping using picture series for the students to write procedure text. There were 17 participants in the research which consisted of 8 females and 9 males. The present research was conducted in two cycles. The results of the finding showed that (1) mind mapping using picture series made the students interested to learn English writing. Before the actions were conducted, the students were less motivated in the teaching and learning process. After the implementation of the actions, they were more enthusiastic to get involved in the teaching and learning process. They became active and paid attention during the lesson. Besides, the students were autonomous in learning without depending on their friend’s works in doing the tasks; (2) The application of mind mapping using picture series can improve students’ skill in writing procedure text at class XI SMKN 1 Kamipang in the Academic Year 2019-2020. Based on the calculation of the percentage, the students who achieved score 65 and more were 100 %. It was higher than 80%. It can be concluded that the classroom action research was categorized successfully. In conclusion, the application of mind mapping using picture series can make the students interested in learning English writing and it also can improve the students’ writing skill of procedure text.